Unlocking CO2’s potential: exploring graphene-based catalysts for sustainable chemicals and fuels production - Srinivaas Masimukku; Yen-Yi Lee; Rajender Boddula; Aanchal Agarwal; Bo-Wun Huang; Guo-Ping Chang-Chien; Kapa Keharika; Ramyakrishna Pothu; Noora Al-Qahtani (Green Chemistry Letters and Reviews)
Exacerbation of anthropogenic emissions, particularly CO2, poses a peril to our planet. Carbon Capture, Utilization, and Storage (CCUS) technologies offer a promising avenue for combatting climate change by transforming CO2 into valuable resources. Graphene-based materials stand out among the catalysts exhibiting significant potential, owing to their remarkable characteristics such as extensive surface area, superior electrical conductivity, and adjustable surface chemistry, which make them well-suited for CO2 conversion applications. The primary focus lies in the synthesis of C1 chemicals (e.g.: formaldehyde, formic acid, and methanol) and C2 chemicals (e.g.: acetic acid, ethanol, methyl formate, and oxy-methylene-ether) as viable alternative choices. Thus far, elucidating the intricate reaction mechanisms of CO2 conversion, including synthesis, selectivity, and efficacy of heterogeneous catalysts, has been examined by assessing their performance, reaction pathways, and enhancements achieved through the integration of various methodologies such as electro/thermo/bio/photo/photothermal/photoelectro-chemical approaches. Selective utilization of resultant products also emerges as a critical point requiring attention. This comprehensive review serves as a pivotal exploration into the conversion of CO2 into fuels and chemicals, highlighting the significance of designing and synthesizing graphene catalysts using the aforementioned methodologies, thereby underscoring their substantial potential as a crucial technology for advancing sustainable CO2 utilization towards combating climate change.